An Unusual Case of a Forgotten Intrauterine Contraceptive Device for 25 Years Presented with Ectopic Pregnancy at AMDA Hospital, Damak, Nepal - Budhathoki, Bimala; Sharma, P; Dhakal, N; Sah, R (Birat Journal of Health Sciences, 2017)
Intrauterine contraceptive device (IUCD), Copper T-380A, is widely used by more than one million women around the world. It is a long acting, reversible device with higher safety, low cost and low failure rate profile. Hereby, we reported a case of ectopic pregnancy with a forgotten IUCD. She was a 42 year woman who had forgotten the IUCD placed in her uterus 25 years back. She was totally unaware of the follow up visits, its removal and that IUCD was causing a problem to conceive for the second time. The inserted IUCD was incidentally discovered on ultrasonography, when she presented with history of lower abdominal pain and vaginal bleeding. On investgation, she had right tubal pregnancy with moderate fluid in pelvic cavity. So, emergency laparotomy was performed followed by right salphingectomy and removal of IUCD.Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 142-144